1995
DOI: 10.1111/j.1398-9995.1995.tb02483.x
|View full text |Cite
|
Sign up to set email alerts
|

Mite allergens in relation to home conditions and sensitization of asthmatic children from three climatic regions

Abstract: We investigated the levels of mite (Der p I and Der f I) allergen in dust from bedrooms, living rooms, kitchens, and bathrooms from 130 homes of asthmatic children in three climatic zones of Sweden. Bedroom dust samples included the child's mattress, carpets, floors, and other plain surfaces. Living-room dust samples were taken from sofas and other furniture, carpets, floors, and other plain surfaces. The allergen levels were related to home characteristics, including absolute indoor humidity (AIH), relative h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
77
4
4

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(98 citation statements)
references
References 22 publications
13
77
4
4
Order By: Relevance
“…The reason for this is unclear but may reflect systematic differences in domestic ventilation. Conversely, MUNIR et al [18], in a survey of 126 homes, reported higher levels of Der p 1 in the homes of smokers. The present results showed a trend towards increasing Der p 1 concentrations in the living room carpets and mattresses of homes with more inhabitants and, as a corollary, in the mattresses of children with more older siblings.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this is unclear but may reflect systematic differences in domestic ventilation. Conversely, MUNIR et al [18], in a survey of 126 homes, reported higher levels of Der p 1 in the homes of smokers. The present results showed a trend towards increasing Der p 1 concentrations in the living room carpets and mattresses of homes with more inhabitants and, as a corollary, in the mattresses of children with more older siblings.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true during the colder seasons. Although in areas with lower humidity indoor dampness is probably more important than outdoor humidity in the domestic development of mites (20), the high outdoor humidity in Taiwan (monthly average 68-80%; Figure 2C) could have been an important determinant of the indoor humidity. The results of this survey suggest that exposure to dust mites or other humidity sensitive allergens was elevated in the children from warm and humid areas in Taiwan.…”
Section: Discussionmentioning
confidence: 99%
“…House dust mite literature consisted of laboratory tests (Arlian, 1992;Arlian et al, 1998), and environmental sampling of dust mite allergens (Munir et al, 1995;Sundell et al, 1995;Arlian et al, 2001;Howieson et al, 2003), with test conditions shown in Figure 2. Arlian (1992) With a brief (2 or 4 hour) exposure to 75% RH, dust mites were unable to complete the entire life cycle, but they laid eggs and many adult females survived.…”
Section: House Dust Mites (Hdm)mentioning
confidence: 99%